Metal / CFRTP composite structure

By preparing anode oxide film on the metal surface and laser welding, the problem of low welding strength and unstable connecting performance of metal and CFRTP connection is solved, and high -strength and stable metal/CFRTP composite structures are achieved.

CN222403928UActive Publication Date: 2025-01-28NAT HIGH SPEED TRAIN QINGDAO TECH INNOVATION CENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420612595.5
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2025-01-28
Estimated Expiration
2034-03-27

AI Technical Summary

Technical Problem

In the prior art, when connecting metals and CFRTP, the welding strength is low and the joint performance is unstable, making it difficult to achieve high-strength connection.

Method used

By preparing anode oxide film on the metal surface, and using laser welding technology, the melting of CFRTP materials is welded on the metal surface to form a mechanical chimeric structure and chemical bonding, thereby improving the welding strength.

Benefits of technology

It significantly improves the binding strength and stability of the metal/CFRTP composite structure, so that the shear force of the 6061 aluminum alloy/CF_PA66 connector has been increased from 2270N to 6513N, an increase of nearly 1.87 times, and the shear force fluctuations do not exceed 200N.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222403928U_ABST
    Figure CN222403928U_ABST
Patent Text Reader

Abstract

The utility model provides a metal / CFRTP (carbon fiber reinforced thermoplastic elastomer) composite structure. The metal / CFRTP composite structure comprises a lap joint of metal and CFRTP, the lap joint is specifically a lap joint formed by welding metal and a CFRTP material; in the lap joint, the metal surface is provided with an anodic oxide film. According to the metal / CFRTP composite structure, the anode oxide film is arranged in the metal / CFRTP composite structure, so that the metal / CFRTP composite structure with higher bonding strength is obtained. The anodic oxidation film is prepared on the metal surface, molten resin flows into oxidation film holes, mechanical embedding is formed between the CFRTP and the metal, meanwhile, the oxidation film can improve the surface energy of the metal, the wettability of the resin on the metal surface is improved, the mechanical embedding and chemical bonding effect between the metal and the CFRTP is promoted, and therefore the metal surface can be improved. And therefore, the bonding strength of laser connection between the metal and the CFRTP plate is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of metal / CFRTP composite structure preparation, and relates to a metal / CFRTP composite structure. Background Art

[0002] CFRTP (carbon fiber reinforced thermoplastic composite material) has the advantages of high specific strength, specific modulus, corrosion resistance, etc., and has become an alternative material for achieving further lightweight engineering applications. Metals or lightweight alloys have high specific strength, corrosion resistance and heat resistance, and have broad application prospects in the aerospace and rail transportation industries. Therefore, connecting the two materials is an effective way to achieve lightweight.

[0003] At present, common methods for connecting metals and CFRTP include riveting, bonding and welding (thermal connection). Mechanical connection can provide higher connection strength, but it destroys the original carbon fiber structure, resulting in stress concentration, which is not conducive to the fatigue performance of the joint. Adhesives are easy to operate and low in cost, but have poor environmental reliability. In a hot and humid environment, the performance of the joint drops sharply. In the welding process, resistance heating welding will leave residual heating elements inside the joint, affecting the performance of the joint, and ultrasonic welding will destroy the reinforced fiber structure of the composite material in the joint, making it difficult to achieve further improvement in strength.

[0004] Laser welding is an effective method to achieve high-quality connection between CFRTP and metal. However, the current direct connection between CFRTP and metal has low welding strength, and it is impossible to obtain a high-strength connection joint. At the same time, there is a problem of unstable performance of the connection joint. At present, the existing technology for connecting metal and CFRTP mainly improves the strength of the joint by preparing micro-textures on the metal surface, and mainly considers strengthening the joint from the perspective of mechanical interlocking. However, there is a problem that the resin cannot completely fill the micro-texture on the metal surface, resulting in weak mechanical interlocking, and it is impossible to obtain a high-strength connection joint. At the same time, there is a problem of unstable performance of the connection joint. For example, a technical solution has been disclosed, which adds a layer of resin material combined with a micro-texture setting between the metal and CFRTP, and connects the metal and CFRTP butt joint by laser. However, the joint strength is relatively low, only about 600N, and the process is relatively cumbersome.

[0005] Therefore, how to find a more suitable structure to solve the above-mentioned problems of metal / CFRTP welding materials and obtain a metal / CFRTP welded composite structure with higher strength has become one of the urgent problems to be solved by many front-line researchers in the industry. Utility Model Content

[0006] In view of this, the technical problem to be solved by the utility model is to provide a metal / CFRTP composite structure. The metal / CFRTP composite structure provided by the utility model has a more excellent bonding strength. Moreover, the preparation process is simple, the conditions are mild, and the controllability is good, which is more suitable for industrial promotion and application.

[0007] The utility model provides a metal / CFRTP composite structure, the metal / CFRTP composite structure comprises a lap joint of metal and CFRTP;

[0008] The lap joint is specifically a lap joint welded between metal and CFRTP material;

[0009] In the lap joint, the metal surface has an anodic oxide film.

[0010] Preferably, in the lap joint, the anodized film is located between the metal and the CFRTP material;

[0011] In the lap joint, the CFRTP material is melt-welded to the metal surface;

[0012] The welding is laser welding.

[0013] Preferably, the anodized film is a rough anodized film;

[0014] The rough anodized film is filled with CFRTP material;

[0015] The welding surface of the lap joint has a mechanical interlocking structure.

[0016] Preferably, the thickness of the anodized film is 0.2 to 0.9 μm;

[0017] The rough anodized film is specifically a rough and porous anodized film;

[0018] In the lap joint, the CFRTP material is melt-welded in the anodized film on the metal surface.

[0019] Preferably, the pores of the anodized film are filled with CFRTP material;

[0020] The pores are specifically nanoscale holes;

[0021] After the laser welding, the CFRTP material melts into the pores of the anodized film and forms a mechanical interlocking structure after cooling.

[0022] Preferably, the pores in the anodized film have a pore size of 20 to 50 nm;

[0023] The depth of the pores in the anodized film is 150 to 700 nm;

[0024] The metal includes one or more of aluminum alloy, stainless steel, magnesium alloy and titanium alloy.

[0025] Preferably, the length and width plane of the metal overlaps the length and width plane of the CFRTP material;

[0026] The area of ​​the lap joint accounts for 4% to 50% of the total area of ​​the metal.

[0027] Preferably, the area of ​​the lap joint accounts for 4% to 50% of the total area of ​​the CFRTP material;

[0028] The shear force / lap width of the lap joint is 250-270 N / mm.

[0029] Preferably, in the lap joint, the length dimension of the metal is 40 to 600 mm;

[0030] In the lap joint, the width dimension of the metal is 30 to 500 mm;

[0031] In the lap joint, the thickness dimension of the metal is 1 to 8 mm.

[0032] Preferably, in the lap joint, the length dimension of the CFRTP material is 40 to 600 mm;

[0033] In the lap joint, the width dimension of the CFRTP material is 20 to 400 mm;

[0034] In the lap joint, the thickness dimension of the CFRTP material is 2 to 6 mm.

[0035] The utility model provides a metal / CFRTP composite structure, the metal / CFRTP composite structure includes a lap joint between metal and CFRTP; the lap joint is specifically a lap joint welded between metal and CFRTP material; in the lap joint, the metal surface has an anodic oxide film. Compared with the prior art, in order to solve the problem of weak interface bonding between metal and CFRTP, although the previous technical solutions also disclosed a technical solution combining micro-arc oxidation with laser welding, the lap strength still needs to be improved, and the shear force is only increased to about 3000N. The utility model believes that although laser welding is an effective method to achieve high-quality connection between CFRTP and metal, the direct connection between CFRTP and metal has a low welding strength, and especially in combination with the anodizing process, supplemented by specific control parameters, it can have a more excellent technical effect.

[0036] Based on this, the utility model provides a metal / CFRTP composite structure with higher bonding strength and greater stability. The utility model sets an anodic oxide film on the metal surface, and the molten resin flows into the pores of the oxide film, so that the CFRTP and the metal form a mechanical fit. At the same time, the oxide film increases the surface energy of the metal, promotes the chemical bonding between the CFRTP and the metal, and thus improves the welding strength of the metal and the CFRTP.

[0037] The metal / CFRTP composite structure provided by the utility model first prepares a nano-scale porous oxide film on the surface of the metal substrate through an anodic oxidation process, and then stacks and fixes the CFRTP plate and the treated metal substrate to be connected, and completes the laser connection under a certain pressure to obtain a firm joint. The utility model improves the wettability of the resin on the metal surface by preparing an anodic oxide film on the metal surface, promotes the mechanical interlocking and chemical bonding between the metal and the CFRTP, and thus improves the bonding strength of the laser connection between the metal and the CFRTP plate.

[0038] The metal / CFRTP composite structure provided by the utility model has an anodic oxide film with a specific structure, which better improves the wettability of the metal surface, promotes the interface bonding with the molten CFRTP, increases the contact area between CFRTP and the metal, and effectively improves the mechanical interlocking effect between the metal and CFRTP. At the same time, the oxide film changes the surface state of the metal substrate, promotes the chemical bonding between the metal and CFRTP, and further improves the connection strength by controlling the specific parameters of the metal and CFRTP welding process, thereby ultimately significantly improving the strength of the metal and CFRTP connection joint.

[0039] Experimental results show that the metal / CFRTP composite structure provided by the utility model increases the shear force of the 6061 aluminum alloy / CF_PA66 joint from 2270N to 6513N, an increase of nearly 1.87 times, and the shear force fluctuation does not exceed 200N. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 A schematic diagram of the structure of a lap joint in a metal / CFRTP composite structure provided by the utility model;

[0041] Figure 2 This is a structural diagram of the laser welding system of the metal / CFRTP composite structure provided by the utility model. DETAILED DESCRIPTION

[0042] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention rather than limiting the patent requirements of the present invention.

[0043] All raw materials of the present invention have no particular restrictions on their sources, and can be purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0044] There is no particular restriction on the purity of all raw materials in the present invention. The present invention preferably uses industrial pure materials or materials with conventional purity requirements in the field of metal / CFRTP composite structure preparation.

[0045] All the raw materials of the utility model, their brands and abbreviations are conventional brands and abbreviations in the field, and each brand and abbreviation is clear and definite in the field of its related use. Those skilled in the art can purchase them from the market or prepare them by conventional methods according to the brands, abbreviations and corresponding uses.

[0046] The abbreviations of the processes used in the present invention are all conventional abbreviations in the field. The specific steps and conventional parameters of each abbreviation are clear and definite in its relevant field. Those skilled in the art can implement them in a conventional way based on the abbreviations.

[0047] CFRTP: Carbon Fiber Reinforced Thermoplastic Composites

[0048] Anodizing: The metal product is used as the anode and placed in an electrolyte solution. Through the action of electrolysis, a nanoporous metal film is formed on its surface.

[0049] The utility model provides a metal / CFRTP composite structure, the metal / CFRTP composite structure comprises a lap joint of metal and CFRTP;

[0050] The lap joint is specifically a lap joint welded between metal and CFRTP material;

[0051] In the lap joint, the metal surface has an anodic oxide film.

[0052] In the present invention, in the lap joint, the anodic oxide film is preferably located between the metal and the CFRTP material;

[0053] In the utility model, in the lap joint, the CFRTP material is preferably melt-welded on the metal surface.

[0054] In the present invention, the welding is preferably laser welding.

[0055] In the present invention, the anodized film is preferably a rough anodized film.

[0056] In the present invention, the rough anodized film is preferably filled with CFRTP material.

[0057] In the present invention, the welding surface of the lap joint preferably has a mechanical interlocking structure.

[0058] In the present invention, the thickness of the anodized film is preferably 0.2 to 0.9 μm, more preferably 0.25 to 0.65 μm, and even more preferably 0.3 to 0.5 μm.

[0059] In the present invention, the rough anodized film is preferably a rough and porous anodized film.

[0060] In the utility model, in the lap joint, the CFRTP material is preferably melt-welded in the anodized film on the metal surface.

[0061] In the present invention, the pores of the anodized film are preferably filled with CFRTP material.

[0062] In the present invention, the pores are preferably nanoscale holes.

[0063] In the utility model, after the laser welding, the CFRTP material is preferably melted into the pores of the anodized film, and a mechanical interlocking structure is formed after cooling.

[0064] In the present invention, the pore diameter of the pores in the anodized film is preferably 20 to 50 nm, more preferably 25 to 45 nm, more preferably 30 to 40 nm, and may also be 10 to 50 nm.

[0065] In the present invention, the depth of the pores in the anodized film is preferably 150 to 700 nm, more preferably 200 to 600 nm, and even more preferably 250 to 350 nm.

[0066] In the present invention, the metal preferably includes one or more of aluminum alloy, stainless steel, magnesium alloy, and titanium alloy.

[0067] In the present invention, the length and width plane of the metal preferably overlaps with the length and width plane of the CFRTP material.

[0068] In the present invention, the area of ​​the lap joint preferably accounts for 4% to 50% of the total area of ​​the metal.

[0069] In the present invention, the area of ​​the lap joint preferably accounts for 4% to 50% of the total area of ​​the CFRTP material, more preferably 14% to 40%, and more preferably 24% to 30%.

[0070] In the utility model, the shear force / lap width of the lap joint is 250-270 N / mm.

[0071] In the utility model, in the lap joint, the length direction dimension of the metal is preferably 40 to 600 mm, more preferably 50 to 400 mm, and more preferably 60 to 150 mm.

[0072] In the utility model, in the lap joint, the width dimension of the metal is preferably 30 to 500 mm, more preferably 35 to 200 mm, and more preferably 40 to 80 mm.

[0073] In the utility model, in the lap joint, the thickness dimension of the metal is preferably 1 to 8 mm, more preferably 1 to 4.5 mm, more preferably 1 to 3 mm, and more preferably 1.5 to 2.5 mm.

[0074] In the utility model, in the lap joint, the length direction dimension of the CFRTP material is preferably 40 to 600 mm, more preferably 45 to 200 mm, and more preferably 50 to 70 mm.

[0075] In the utility model, in the lap joint, the width dimension of the CFRTP material is preferably 20 to 400 mm, more preferably 25 to 100 mm, and more preferably 30 to 50 mm.

[0076] In the utility model, in the lap joint, the thickness dimension of the CFRTP material is preferably 2 to 6 mm, more preferably 2.5 to 5.5 mm, more preferably 2.5 to 5 mm, and more preferably 3 to 4.5 mm.

[0077] See also Figure 1 , Figure 1 The schematic diagram of the structure of the lap joint in the metal / CFRTP composite structure provided by the utility model is shown in FIG. 1 is metal, 2 is CFRTP material, and 3 is an anodic oxide film.

[0078] The utility model provides the application of anodizing process in preparing metal / CFRTP composite structure;

[0079] The preparation is specifically laser welding preparation.

[0080] In the present invention, the application is preferably to anodize the metal surface to form an anodized film before laser welding.

[0081] In the present invention, the anodized film is preferably a rough and porous anodized film.

[0082] In the present invention, the metal / CFRTP composite structure preferably includes a lap joint of metal and CFRTP.

[0083] In the present invention, the lap joint is preferably a lap joint welded between metal and CFRTP material;

[0084] In the present invention, the welding surface of the lap joint preferably has a mechanical interlocking structure.

[0085] In the utility model, in the lap joint, the CFRTP material is preferably melt-welded on the metal surface.

[0086] In the present invention, the pores of the anodized film are preferably filled with CFRTP material.

[0087] In the present invention, the pores are preferably nanoscale holes.

[0088] In the present invention, after the laser welding, the CFRTP material is preferably melted into the pores of the anodized film, and a mechanical interlocking structure is formed after cooling.

[0089] In the present invention, the pore size of the anodic oxide film is preferably 20 to 50 nm, more preferably 25 to 45 nm, more preferably 30 to 40 nm, and may also be 10 to 50 nm.

[0090] In the present invention, the depth of the pores in the anodized film is preferably 150 to 700 nm, more preferably 200 to 600 nm, and even more preferably 250 to 350 nm.

[0091] In the present invention, the thickness of the anodized film is preferably 200 nm to 900 nm, more preferably 250 nm to 650 nm, and preferably 300 nm to 500 nm.

[0092] In the present invention, the metal preferably includes one or more of aluminum alloy, stainless steel, magnesium alloy, and titanium alloy, and more preferably aluminum alloy, stainless steel, magnesium alloy, or titanium alloy.

[0093] In the present invention, the length and width plane of the metal preferably overlaps with the length and width plane of the CFRTP material.

[0094] In the present invention, the area of ​​the lap joint preferably accounts for 4% to 50% of the total area of ​​the metal, more preferably 14% to 40%, and more preferably 24% to 30%.

[0095] In the present invention, the area of ​​the lap joint preferably accounts for 4% to 50% of the total area of ​​the CFRTP material, more preferably 14% to 40%, and more preferably 24% to 30%.

[0096] In the present invention, the voltage of the anodic oxidation is preferably 9 to 15V, more preferably 9 to 14V, and more preferably 9 to 12V.

[0097] In the present invention, the anodization time is preferably 10 to 40 minutes, more preferably 15 to 35 minutes, and more preferably 20 to 30 minutes.

[0098] In the present invention, the laser power of the laser welding is preferably 400-1500W, more preferably 400-1000W, and more preferably 400-600W.

[0099] In the present invention, the scanning speed of the laser welding is preferably 0.2-0.6 m / min, more preferably 0.25-0.55 m / min, more preferably 0.3-0.5 m / min, and more preferably 0.35-0.45 m / min.

[0100] In the present invention, the defocus amount of the laser welding is preferably +5 to +20 mm, more preferably +8 to +17 mm, and more preferably +10 to +13 mm.

[0101] In the present invention, the laser inclination angle of the laser welding is preferably 10° to 30°, more preferably 10° to 26°, and more preferably 10° to 15°.

[0102] In the present invention, the pressure of the laser welding is preferably 50-400N, more preferably 50-300N, more preferably 50-200N, and more preferably 50-100N.

[0103] In the utility model, in the lap joint, the length direction dimension of the metal is preferably 40 to 600 mm, more preferably 50 to 400 mm, and more preferably 60 to 150 mm.

[0104] In the utility model, in the lap joint, the width dimension of the metal is preferably 30 to 500 mm, more preferably 35 to 200 mm, and more preferably 40 to 80 mm.

[0105] In the utility model, in the lap joint, the thickness dimension of the metal is preferably 1 to 4.5 mm, more preferably 1 to 3 mm, and more preferably 1.5 to 2.5 mm.

[0106] In the utility model, in the lap joint, the length direction dimension of the CFRTP material is preferably 40 to 600 mm, more preferably 45 to 200 mm, and more preferably 50 to 70 mm.

[0107] In the utility model, in the lap joint, the width dimension of the CFRTP material is preferably 20 to 400 mm, more preferably 25 to 100 mm, and more preferably 30 to 50 mm.

[0108] In the utility model, in the lap joint, the thickness dimension of the CFRTP material is preferably 2 to 6 mm, more preferably 2.5 to 5.5 mm, more preferably 2.5 to 5 mm, and more preferably 3 to 4.5 mm.

[0109] The utility model particularly applies the anodizing process and the laser welding process together in the preparation process of the metal / CFRTP composite structure. Compared with micro-arc oxidation, anodizing can prepare oxide film pores of a few nanometers to tens of nanometers, and the oxide film pores are relatively shallow, which can increase the contact area between the resin and the aluminum alloy during the welding of aluminum alloy and CFRTP, and ensure that the resin can completely fill the oxide film pores, thereby improving the interface bonding strength.

[0110] The utility model prepares an anodic oxide film on the surface of a metal such as an aluminum alloy by anodizing, controls the pore diameter of the oxide film to be 20 to 50 nm, the pore depth to be 150 to 700 nm, and the thickness of the oxide film to be 200 to 900 nm, and then performs laser welding with CFRTP. Through the synergistic effect of anodizing and welding processes, the resin is melted to fully fill the anodized pores, thereby improving the strength of the welded joint.

[0111] The utility model provides a method for preparing a metal / CFRTP composite structure, comprising the following steps:

[0112] 1) After cleaning the surface of the joint of the metal substrate to be welded, anodizing is performed to form an anodic oxide film on the surface of the joint of the metal substrate to obtain a metal substrate to be used;

[0113] After cleaning the surface of the CFRTP joint to be welded, a CFRTP material to be used is obtained;

[0114] 2) Overlap the welding surface of the to-be-used metal matrix joint obtained in the above steps with the welding surface of the to-be-used CFRTP material, and perform laser welding by laser scanning and heating the metal matrix under a certain pressure to obtain a metal / CFRTP composite structure.

[0115] The utility model first cleans the surface of the joint of the metal substrate to be welded, and then performs anodization to form an anodized film on the surface of the joint of the metal substrate to obtain the metal substrate to be used;

[0116] After cleaning the surface of the CFRTP joint to be welded, the CFRTP material to be used is obtained.

[0117] In the present invention, the surface cleaning method of the joint of the metal substrate preferably includes one or more of alkali washing, acid washing and water washing, and more preferably includes multiple of alkali washing, acid washing and water washing.

[0118] In the present invention, the concentration of the alkaline solution for alkaline washing is preferably 100 to 300 g / L, more preferably 140 to 260 g / L, and more preferably 180 to 250 g / L.

[0119] In the present invention, the concentration of the pickling acid solution is preferably 50 to 200 g / L, more preferably 80 to 170 g / L, and more preferably 100 to 140 g / L.

[0120] In the present invention, the surface cleaning method of the CFRTP preferably includes ultrasonic cleaning with an organic solvent.

[0121] In the present invention, the organic solvent ultrasonic cleaning time is preferably 30 to 40 minutes, more preferably 32 to 38 minutes, and more preferably 34 to 36 minutes.

[0122] In the present invention, the voltage of the anodic oxidation is preferably 9 to 15V, more preferably 9 to 14V, and more preferably 9 to 12V.

[0123] In the present invention, the anodization time is preferably 10 to 40 minutes, more preferably 15 to 35 minutes, and more preferably 20 to 30 minutes.

[0124] In the present invention, the concentration of the oxidizing solution used for the anodizing is preferably 100 to 200 g / L, more preferably 120 to 180 g / L, and more preferably 140 to 160 g / L.

[0125] In the present invention, the oxidizing liquid preferably includes one or more of phosphoric acid, sulfuric acid and boric acid, more preferably phosphoric acid, sulfuric acid or boric acid.

[0126] In the present invention, the pore size of the pores in the anodized film is preferably 20 to 50 nm, more preferably 25 to 45 nm, and more preferably 30 to 40 nm.

[0127] In the present invention, the depth of the pores in the anodized film is preferably 150 to 700 nm, more preferably 200 to 600 nm, and even more preferably 250 to 350 nm.

[0128] Finally, the utility model overlaps the welding surface of the standby metal matrix joint obtained in the above steps with the welding surface of the standby CFRTP material, and uses laser scanning to heat the metal matrix for laser welding under a certain pressure to obtain a metal / CFRTP composite structure.

[0129] In the present invention, the certain pressure is preferably 50-400N, more preferably 50-350N, more preferably 50-300N, and more preferably 50-150N.

[0130] In the present invention, the laser power of the laser welding is preferably 400-1500W, more preferably 400-1000W, and more preferably 400-600W.

[0131] In the present invention, the scanning speed of the laser welding is preferably 0.2-0.6 m / min, more preferably 0.25-0.55 m / min, more preferably 0.3-0.5 m / min, and more preferably 0.35-0.45 m / min.

[0132] In the present invention, the defocus amount of the laser welding is preferably +5 to +20 mm, more preferably +8 to +17 mm, and more preferably +10 to +13 mm.

[0133] In the present invention, the laser inclination angle of the laser welding is preferably 10° to 30°, more preferably 10° to 26°, and more preferably 10° to 15°.

[0134] In the present invention, the flow rate of the shielding gas for laser welding is preferably 15 to 25 L / min, more preferably 17 to 23 L / min, and more preferably 19 to 21 L / min.

[0135] The metal / CFRTP composite structure provided by the utility model prepares a nano-scale porous oxide film on the surface of the metal substrate, stacks and fixes the CFRTP plate and the treated metal substrate to be connected, and completes the laser connection under a certain pressure to obtain a firm joint. The utility model sets an anodic oxide film on the metal surface to improve the wettability of the resin on the metal surface, promotes the mechanical interlocking and chemical bonding between the metal and CFRTP, and thus improves the bonding strength of the laser connection between the metal and the CFRTP plate.

[0136] The utility model is a complete and detailed overall technical solution to better improve the welding strength and stability of the metal / CFRTP composite structure. The above-mentioned metal / CFRTP laser connection method can specifically include the following contents:

[0137] A laser connection method for metal / carbon fiber reinforced thermoplastic composite (CFRTP) comprises the following steps:

[0138] (1) Remove the oxide film on the metal surface and the oil stain on the CFRTP surface. The method for removing the oxide film on the metal surface is to soak the metal substrate in a 100g / L to 300g / L NaOH solution for 3 to 10 minutes, rinse it with clean water, soak it in a 50g / L to 200g / L H3PO4 solution for 1 to 5 minutes, and then rinse it with clean water; the method for removing the oil stain on the CFRTP surface is to ultrasonically clean the CFRTP in alcohol for 30 to 40 minutes, and then dry it at 80 to 100°C for 2 to 4 hours.

[0139] (2) The surface of the metal substrate obtained in (1) is used to prepare an anodic oxide film using an anodic oxidation system. The processing technology is that the anodic oxidation voltage is 9 to 15 V, the oxidation time is 10 to 40 min, the concentration of the oxidation liquid is 100 g / L to 200 g / L, the pore diameter of the prepared oxide film is 20 to 50 nm, the depth of the pore is 150 to 700 nm, and the thickness of the oxide film is 200 nm to 900 nm.

[0140] (3) The metal substrate with an anodized film prepared in (2) is stacked together with the CF_PA66 sheet, and fixed with a clamping fixture to make the metal substrate and the CF_PA66 sheet fit tightly together. The surface of the metal sheet is scanned by laser, and the heat is transferred from the metal surface to the connection interface to melt the CF_PA66 sheet. The molten resin wets and spreads on the surface of the metal substrate. Under the action of the interface pressure, the molten resin enters the holes of the oxide film on the surface of the metal substrate, thereby achieving the connection between the 6061 aluminum alloy substrate and the CF_PA66 sheet. The laser connection process is as follows: laser power 400~1500W, scanning speed 0.2~0.6m / min, defocus +5~+20mm, pressure 50~400N, laser inclination angle 10°~30°, and protective gas flow rate 15~25L / min.

[0141] The utility model also provides a welding system of a metal / CFRTP composite structure, comprising a base;

[0142] A pressing tool disposed on a base;

[0143] The pressing tool is provided with a vacant area for welding;

[0144] A supporting tooling provided corresponding to the pressing tooling;

[0145] A locking device connected to the pressing tool and the base respectively;

[0146] A pressure sensor connected to the locking device;

[0147] Laser welding device.

[0148] In the present invention, the vacant area preferably includes a rectangular or square vacant area.

[0149] In the present invention, the area of ​​the vacant region accounts for preferably 20% to 30% of the total area of ​​the pressing tool, more preferably 22% to 28%, and even more preferably 24% to 26%.

[0150] In the present utility model, the pressing tool preferably has a rectangular parallelepiped structure.

[0151] In the present invention, the vacant area preferably has a stepped hole structure.

[0152] In the present invention, the upper surface of the pressing tooling away from the supporting tooling is preferably the top surface, and the lower surface adjacent to the supporting tooling is preferably the bottom surface.

[0153] In the present invention, the area of ​​the vacant area on the top surface of the pressing tool is preferably larger than the area on the bottom surface of the pressing tool.

[0154] In the present invention, the height of the step from the top surface in the vacant area preferably accounts for 80% to 90% of the height of the vacant area, more preferably 82% to 88%, and more preferably 84% to 86%.

[0155] In the present invention, the welding head of the laser welding device is preferably located above the vacant area.

[0156] In the present invention, the emitting end of the laser emitter on the welding head is preferably located above the top surface of the clamping fixture.

[0157] In the utility model, the laser emitter on the welding head is preferably arranged at an angle of 10° to 30° to the bottom surface of the pressing tool, more preferably at an angle of 10° to 26°, and even more preferably at an angle of 10° to 15°.

[0158] In the present invention, the distance between the emitting end of the laser emitter and the bottom surface of the pressing tool is preferably 250-270 mm, more preferably 254-266 mm, and more preferably 258-262 mm.

[0159] In the present invention, the outlet end of the shielding gas conduit of the laser welding device is preferably located between the step of the vacant area and the bottom surface of the pressing tool, that is, the top end (outlet end) of the shielding gas conduit is located below the step.

[0160] In the present invention, the outlet end of the protective gas duct is preferably arranged at an angle of 30° to 45° to the bottom surface of the pressing tool, more preferably at an angle of 33° to 42°, and even more preferably at an angle of 36° to 39°.

[0161] In the utility model, the distance between the outlet end of the protective gas duct and the bottom surface of the pressing tool is preferably 3 to 15 mm, more preferably 3 to 12 mm, and more preferably 3 to 10 mm.

[0162] In the present invention, the locking device preferably includes a first locking device and a second locking device.

[0163] In the present invention, one end of the first locking device is preferably pressed on one end of the pressing tool, and the other end is preferably associated with the base.

[0164] In the present invention, one end of the second locking device is preferably pressed on the other end of the pressing tool, and the other end is preferably associated with the base.

[0165] In the utility model, a pressure-adjusting nut is preferably provided on the first locking device.

[0166] In the utility model, a pressure-adjusting nut is preferably provided on the second locking device.

[0167] In the present invention, a first pressure sensitive element of a pressure sensor is preferably provided between one end of the first locking device and one end of the pressing tool.

[0168] In the present invention, a second pressure sensitive element of a pressure sensor is preferably provided between one end of the second locking device and the other end of the pressing tool.

[0169] In the present invention, the first pressure sensitive element and the second pressure sensitive element are preferably respectively connected to a signal processing unit of a pressure sensor.

[0170] In the present invention, a CFRTP composite material sheet and a metal sheet overlapping the CFRTP composite material are preferably provided between the pressing tool and the supporting tool.

[0171] In the present invention, the lower surface of the supporting tooling away from the pressing tooling is preferably the bottom surface, and the upper surface adjacent to the pressing tooling is preferably the top surface.

[0172] In the present invention, the metal sheet is preferably attached to the bottom surface of the pressing tool.

[0173] In the present invention, the CFRTP composite material is preferably attached to the top surface of the supporting tooling.

[0174] In the present invention, the overlap joint between the metal sheet and the CFRTP composite material is preferably located in the vacant area.

[0175] In the present invention, an anodic oxidation film is preferably provided between the contact surfaces of the overlapped joint of the metal sheet and the CFRTP composite material.

[0176] In the present invention, the anodized film is preferably a porous structure.

[0177] See also Figure 2 , Figure 2 The structure diagram of the laser welding system of the metal / CFRTP composite structure provided by the utility model. Among them, 1 is a supporting tool, 2 is a clamping tool, 3 is a first locking device, 4 is a pressure-adjusting nut, 5 is a first pressure-sensitive element, 6 is a second locking device, 7 is a pressure-adjusting nut, 8 is a second pressure-sensitive element, 9 is a pressure sensor, and 10 is a laser welding device. 11 is a CFRTP sheet, and 12 is a metal sheet.

[0178] The above content of the utility model provides a metal / CFRTP composite structure with higher bonding strength and more stability. The utility model sets an anodic oxide film on the metal surface, and the molten resin flows into the pores of the oxide film, so that the CFRTP and the metal form a mechanical fit. At the same time, the oxide film increases the surface energy of the metal, promotes the chemical bonding between CFRTP and the metal, and thus improves the welding strength of the metal and CFRTP.

[0179] The metal / CFRTP composite structure provided by the utility model first prepares a nano-scale porous oxide film on the surface of the metal substrate through an anodic oxidation process, and then stacks and fixes the CFRTP plate and the treated metal substrate to be connected, and completes the laser connection under a certain pressure to obtain a firm joint. The utility model improves the wettability of the resin on the metal surface by preparing an anodic oxide film on the metal surface, promotes the mechanical interlocking and chemical bonding between the metal and the CFRTP, and thus improves the bonding strength of the laser connection between the metal and the CFRTP plate.

[0180] The metal / CFRTP composite structure provided by the utility model has an anodic oxide film with a specific structure, which better improves the wettability of the metal surface, promotes the interface bonding with the molten CFRTP, increases the contact area between CFRTP and the metal, and effectively improves the mechanical interlocking effect between the metal and CFRTP. At the same time, the oxide film changes the surface state of the metal substrate, promotes the chemical bonding between the metal and CFRTP, and further improves the connection strength by controlling the specific parameters of the metal and CFRTP welding process, thereby ultimately significantly improving the strength of the metal and CFRTP connection joint.

[0181] Experimental results show that the metal / CFRTP composite structure provided by the utility model increases the shear force of the 6061 aluminum alloy / CF_PA66 joint from 2270N to 6513N, an increase of nearly 1.87 times, and the shear force fluctuation does not exceed 200N.

[0182] In order to further illustrate the present invention, a metal / CFRTP composite structure provided by the present invention is described in detail below in combination with embodiments. However, it should be understood that these embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention. The protection scope of the present invention is not limited to the following embodiments.

[0183] Example 1

[0184] (1) The carbon fiber reinforced poly(hexamethylene adipamide) (CF_PA66) sheet to be connected is placed in an ultrasonic cleaning machine and cleaned in an alcohol solution for 30 minutes to remove surface oil stains. The cleaned CF_PA66 sheet is then placed in an 80°C drying oven for 2 hours. The 6061 aluminum alloy substrate is placed in a 200 g / L NaOH solution for 5 minutes to remove the surface oxide film, then rinsed with clean water for 10 seconds, and then placed in a 100 g / L H3PO4 solution for 3 minutes to neutralize the residual NaOH on the surface of the aluminum alloy, and then rinsed with clean water for 10 seconds;

[0185] (2) An anodic oxidation film was produced on the surface of the 6061 aluminum alloy substrate treated as above by using an anodic oxidation system, and the processing parameters were set as an oxidation voltage of 12V, an oxidation liquid of 150g / L H3PO4, and an oxidation time of 30min. The obtained oxidation film had a pore size of 30-50nm and a thickness of 600-800nm.

[0186] (3) The 6061 aluminum alloy substrate with an oxide film on the surface obtained in (2) and the CF_PA66 sheet were pressed Figure 2 The 6061 aluminum alloy substrate with an oxide film prepared is stacked with the CF_PA66 sheet and fixed with a clamping fixture to make the metal substrate and the CF_PA66 sheet fit tightly, effectively avoiding the displacement of the two materials during the welding process and ensuring the stability of the welding joint performance.

[0187] (4) The laser connection process is specifically as follows: laser power 450W, laser scanning speed 0.3m / min, defocusing amount +10mm, protective gas argon flow rate 25L / min, and laser deflection angle 10°.

[0188] The shear force test was performed on the components of the same size prepared in the embodiment of the utility model and the comparative example, and the test results are shown in Table 1. Table 1 is the shear force test results of the metal / CFRTP composite structure prepared in the embodiment of the utility model and the comparative example.

[0189] Example 2

[0190] (1) The carbon fiber reinforced poly(hexamethylene adipamide) (CF_PA66) sheet to be connected is placed in an ultrasonic cleaning machine and cleaned in an alcohol solution for 30 minutes to remove surface oil stains. The cleaned CF_PA66 sheet is then placed in an 80°C drying oven for 2 hours. The 6061 aluminum alloy substrate is placed in a 200 g / L NaOH solution for 5 minutes to remove the surface oxide film, then rinsed with clean water for 10 seconds, and then placed in a 100 g / L H3PO4 solution for 3 minutes to neutralize the residual NaOH on the surface of the aluminum alloy, and then rinsed with clean water for 10 seconds;

[0191] (2) An anodic oxidation film was manufactured on the surface of the 6061 aluminum alloy substrate treated as above using an anodic oxidation system, and the processing parameters were set as an oxidation voltage of 9 V, an oxidation liquid of 150 g / L H3PO4, and an oxidation time of 20 min.

[0192] (3) The 6061 aluminum alloy substrate with an oxide film on the surface obtained in (2) and the CF_PA66 sheet were pressed Figure 2 The 6061 aluminum alloy substrate with an oxide film prepared is stacked with the CF_PA66 sheet and fixed with a clamping fixture to make the metal substrate and the CF_PA66 sheet fit tightly, effectively avoiding the displacement of the two materials during the welding process and ensuring the stability of the welding joint performance.

[0193] (4) The laser connection process is specifically as follows: laser power 450W, laser scanning speed 0.3m / min, defocusing amount +10mm, protective gas argon flow rate 25L / min, and laser deflection angle 10°.

[0194] The shear force test was performed on the components of the same size prepared in the embodiment of the utility model and the comparative example, and the test results are shown in Table 1. Table 1 is the shear force test results of the metal / CFRTP composite structure prepared in the embodiment of the utility model and the comparative example.

[0195] Example 3

[0196] (1) The carbon fiber reinforced poly(hexamethylene adipamide) (CF_PA66) sheet to be connected is placed in an ultrasonic cleaning machine and cleaned in an alcohol solution for 30 minutes to remove surface oil stains. The cleaned CF_PA66 sheet is then placed in an 80°C drying oven for 2 hours. The 6061 aluminum alloy substrate is placed in a 200 g / L NaOH solution for 5 minutes to remove the surface oxide film, then rinsed with clean water for 10 seconds, and then placed in a 100 g / L H3PO4 solution for 3 minutes to neutralize the residual NaOH on the surface of the aluminum alloy, and then rinsed with clean water for 10 seconds;

[0197] (2) An anodic oxidation film was manufactured on the surface of the 6061 aluminum alloy substrate treated as above using an anodizing system, and the processing parameters were set as an oxidation voltage of 9 V, an oxidation liquid of 150 g / L H3PO4, and an oxidation time of 30 min.

[0198] (3) The 6061 aluminum alloy substrate with an oxide film on the surface obtained in (2) and the CF_PA66 sheet were pressed Figure 2 The 6061 aluminum alloy substrate with an oxide film prepared is stacked with the CF_PA66 sheet and fixed with a clamping fixture to make the metal substrate and the CF_PA66 sheet fit tightly, effectively avoiding the displacement of the two materials during the welding process and ensuring the stability of the welding joint performance.

[0199] (4) The laser connection process is specifically as follows: laser power 400 W, laser scanning speed 0.3 m / min, defocusing amount +10 mm, protective gas argon flow rate 25 L / min, and laser deflection angle 10°.

[0200] The shear force test was performed on the components of the same size prepared in the embodiment of the utility model and the comparative example, and the test results are shown in Table 1. Table 1 is the shear force test results of the metal / CFRTP composite structure prepared in the embodiment of the utility model and the comparative example.

[0201] Comparative Example 1

[0202] (1) The carbon fiber reinforced poly(hexamethylene adipamide) (CF_PA66) sheet to be connected is placed in an ultrasonic cleaning machine and cleaned in an alcohol solution for 30 minutes to remove surface oil stains. The cleaned CF_PA66 sheet is then placed in an 80°C drying oven for 2 hours. The 6061 aluminum alloy substrate is placed in a 200 g / L NaOH solution for 5 minutes to remove the surface oxide film, then rinsed with clean water for 10 seconds, and then placed in a 100 g / L H3PO4 solution for 3 minutes to neutralize the residual NaOH on the surface of the aluminum alloy, and then rinsed with clean water for 10 seconds;

[0203] (2) An anodic oxidation film was produced on the surface of the 6061 aluminum alloy substrate treated as above by using an anodic oxidation system, and the processing parameters were set as an oxidation voltage of 9 V, an oxidation liquid of 150 g / L H3PO4, and an oxidation time of 5 min.

[0204] (3) The 6061 aluminum alloy substrate with an oxide film on the surface obtained in (2) and the CF_PA66 sheet were pressed Figure 2 The 6061 aluminum alloy substrate with an oxide film prepared is stacked with the CF_PA66 sheet and fixed with a clamping fixture to make the metal substrate and the CF_PA66 sheet fit tightly, effectively avoiding the displacement of the two materials during the welding process and ensuring the stability of the welding joint performance.

[0205] (4) The laser connection process is specifically as follows: laser power 450W, laser scanning speed 0.3m / min, defocusing amount +10mm, protective gas argon flow rate 25L / min, and laser deflection angle 10°.

[0206] Comparative Example 2

[0207] (1) The carbon fiber reinforced poly(hexamethylene adipamide) (CF_PA66) sheet to be connected is placed in an ultrasonic cleaning machine and cleaned in an alcohol solution for 30 minutes to remove surface oil stains. The cleaned CF_PA66 sheet is then placed in an 80°C drying oven for 2 hours. The 6061 aluminum alloy substrate is placed in a 200 g / L NaOH solution for 5 minutes to remove the surface oxide film, then rinsed with clean water for 10 seconds, and then placed in a 100 g / L H3PO4 solution for 3 minutes to neutralize the residual NaOH on the surface of the aluminum alloy, and then rinsed with clean water for 10 seconds;

[0208] (2) An anodic oxidation film was manufactured on the surface of the 6061 aluminum alloy substrate treated as above using an anodic oxidation system, and the processing parameters were set as an oxidation voltage of 9 V, an oxidation liquid of 250 g / L H3PO4, and an oxidation time of 30 min.

[0209] (3) The 6061 aluminum alloy substrate with an oxide film on the surface obtained in (2) and the CF_PA66 sheet were pressed Figure 2 The 6061 aluminum alloy substrate with an oxide film prepared is stacked with the CF_PA66 sheet and fixed with a clamping fixture to make the metal substrate and the CF_PA66 sheet fit tightly, effectively avoiding the displacement of the two materials during the welding process and ensuring the stability of the welding joint performance.

[0210] (4) The laser connection process is specifically as follows: laser power 450W, laser scanning speed 0.3m / min, defocusing amount +10mm, protective gas argon flow rate 25L / min, and laser deflection angle 10°.

[0211] Comparative Example 3

[0212] (1) The carbon fiber reinforced poly(hexamethylene adipamide) (CF_PA66) sheet to be connected is placed in an ultrasonic cleaning machine and cleaned in an alcohol solution for 30 minutes to remove surface oil stains. The cleaned CF_PA66 sheet is then placed in an 80°C drying oven for 2 hours. The 6061 aluminum alloy substrate is placed in a 200 g / L NaOH solution for 5 minutes to remove the surface oxide film, then rinsed with clean water for 10 seconds, and then placed in a 100 g / L H3PO4 solution for 3 minutes to neutralize the residual NaOH on the surface of the aluminum alloy, and then rinsed with clean water for 10 seconds;

[0213] (2) An anodic oxidation film was manufactured on the surface of the 6061 aluminum alloy substrate treated as above using an anodic oxidation system, and the processing parameters were set as an oxidation voltage of 9 V, an oxidation liquid of 150 g / L H3PO4, and an oxidation time of 30 min.

[0214] (3) The 6061 aluminum alloy substrate with an oxide film on the surface obtained in (2) and the CF_PA66 sheet were pressed Figure 2 The 6061 aluminum alloy substrate with an oxide film prepared is stacked with the CF_PA66 sheet and fixed with a clamping fixture to make the metal substrate and the CF_PA66 sheet fit tightly, effectively avoiding the displacement of the two materials during the welding process and ensuring the stability of the welding joint performance.

[0215] (4) The laser connection process is specifically as follows: laser power 300 W, laser scanning speed 0.3 m / min, defocusing amount +10 mm, protective gas argon flow rate 25 L / min, and laser deflection angle 10°.

[0216] Comparative Example 4

[0217] This comparative example provides a non-oxide film metal / CFRTP laser connection method, and uses this method to complete the laser connection of carbon fiber reinforced polyhexamethylene adipamide (CF_PA66), which specifically includes the following steps:

[0218] (1) The carbon fiber reinforced poly(hexamethylene adipamide) (CF_PA66) sheet to be connected is placed in an ultrasonic cleaning machine and cleaned in an alcohol solution for 30 minutes to remove surface oil stains. The cleaned CF_PA66 sheet is then placed in an 80°C drying oven for 2 hours. The 6061 aluminum alloy substrate is placed in a 250 g / L NaOH solution for 5 minutes to remove the surface oxide film, and then rinsed with clean water. It is then placed in a 100 g / L H3PO4 solution for 3 minutes to neutralize the residual NaOH on the surface of the aluminum alloy, and then rinsed with clean water. It is then placed in an ultrasonic cleaning machine and cleaned in deionized water for 15 minutes, and then blown dry with cold air;

[0219] (2) The 6061 aluminum alloy substrate and the CF_PA66 plate in (1) are stacked together and welded by laser. The process parameters are laser power 400 W, laser scanning speed 0.3 m / min, defocus amount +15 mm, protective gas argon flow rate 25 L / min, and laser deflection angle 10° to obtain a 6061 aluminum alloy / CF_PA66 joint.

[0220] The shear force test was performed on the components of the same size prepared in the embodiment and the comparative example. The test results are shown in Table 1.

[0221] Table 1

[0222]

[0223]

[0224] From the comparison of the data in Table 1, it can be seen that by cleaning the metal surface and preparing micro-textures, the shear force of the 6061 aluminum alloy / CF_PA66 joint is increased from 2270N to 6513N, an increase of nearly 1.87 times, and the shear force fluctuation does not exceed 200N.

[0225] The above is a detailed introduction to a metal / CFRTP composite structure provided by the utility model. The principle and implementation method of the utility model are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of ​​the utility model, including the best mode, and also enables any technician in the field to practice the utility model, including manufacturing and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the utility model, the utility model can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the utility model. The scope of patent protection of the utility model is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A metal / CFRTP composite structure, characterized in that: The metal / CFRTP composite structure includes a lap joint of metal and CFRTP; The lap joint is specifically a lap joint welded between metal and CFRTP material; In the lap joint, the metal surface has an anodic oxide film.

2. The metal / CFRTP composite structure according to claim 1, characterized in that: In the lap joint, the anodic oxide film is located between the metal and the CFRTP material; In the lap joint, the CFRTP material is melt-welded to the metal surface; The welding is laser welding.

3. The metal / CFRTP composite structure according to claim 1, characterized in that: The anodized film is specifically a rough anodized film; The rough anodized film is filled with CFRTP material; The welding surface of the lap joint has a mechanical interlocking structure.

4. The metal / CFRTP composite structure according to claim 3, characterized in that: The thickness of the anodized film is 0.2 to 0.9 μm; The rough anodized film is specifically a rough and porous anodized film; In the lap joint, the CFRTP material is melt-welded in the anodized film on the metal surface.

5. The metal / CFRTP composite structure according to claim 3, characterized in that: The pores of the anodized film are filled with CFRTP material; The pores are specifically nanoscale holes; After the welding, the CFRTP material melts into the pores of the anodized film and forms a mechanical interlocking structure after cooling.

6. The metal / CFRTP composite structure according to claim 5, characterized in that: The pores in the anodized film have a pore size of 20 to 50 nm; The depth of the pores in the anodized film is 150 to 700 nm; The metal includes one or more of aluminum alloy, stainless steel, magnesium alloy and titanium alloy.

7. The metal / CFRTP composite structure according to claim 1, characterized in that: The length and width plane of the metal overlaps the length and width plane of the CFRTP material; The area of ​​the lap joint accounts for 4% to 50% of the total area of ​​the metal.

8. The metal / CFRTP composite structure according to claim 1, characterized in that: The area of ​​the lap joint accounts for 4% to 50% of the total area of ​​the CFRTP material; The shear force / lap width of the lap joint is 250-270 N / mm.

9. The metal / CFRTP composite structure according to claim 1, characterized in that: In the lap joint, the length dimension of the metal is 40 to 600 mm; In the lap joint, the width dimension of the metal is 30 to 500 mm; In the lap joint, the thickness dimension of the metal is 1 to 8 mm.

10. The metal / CFRTP composite structure according to claim 1, characterized in that: In the lap joint, the length direction dimension of the CFRTP material is 40 to 600 mm; In the lap joint, the width dimension of the CFRTP material is 20 to 400 mm; In the lap joint, the thickness dimension of the CFRTP material is 2 to 6 mm.